KOMUNIKASI PEMASARAN PARIWISATA DI DESA PAJAR BULAN KABUPATEN MUARA ENIM - Pratiwi, Miftha; Andarini, Rindang Senja; Elfandari, Safitri (Universitas Mataram, 2024)
Tourism is an economic sector that is growing very rapidly and dynamically. Indonesia has a widespread tourism potential. Muara Enim is an area that is rich in tourism potential, some of which has been managed as a tourist destination. In developing this tourist destination, integrated tourism marketing communications is needed which is supported by strong destination branding so that it is able to compete with tourist destinations in other areas. This community service activity aims to increase understanding of tourism marketing communications with the target audience of Karang Taruna members in Pajar Bulan Village, Semende Darat Laut District, Muara Enim Regency, South Sumatra. This activity first begins with a pre-test to measure participants' knowledge before receiving the material, followed by a presentation of material regarding the basics of tourism marketing communication using lecture methods, question and answer session, and ends with a post-test to measure participants' understanding after receiving the material. This service activity succeeded in increasing public understanding of tourism marketing communications. This is evidenced by the increase in the average post-test result of 76,8 from the average score during the pre-test of 55,6. Statistical analysis using the Wilcoxon test shows the Sig value. (2-tailed) 0.000 < 0.05 which means the alternative hypothesis (Ha) is proven. This result has proven that there is a significant difference between the average pre-test score and the average post-test score. This shows that tourism marketing communication training has a significant influence on increasing participants' understanding of important aspects in tourism destination marketing. It can be concluded that over all the implementation of tourism marketing communication training in Pajar Bulan Village has been successful because there has been an increase in understanding.